2002
DOI: 10.1002/ijc.10746
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mitogen‐activated protein kinase phosphatase‐1 (MKP‐1) in primary human ovarian carcinoma

Abstract: The mitogen-activated protein kinase phosphatase-1, MKP-1 (CL100) is involved in inactivation of MAP-kinase pathways, regulation of stress-responses and suppression of apoptosis. We investigated expression of MKP-1 in 90 cases of primary ovarian tumors, 11 normal ovaries as well as 4 ovarian carcinoma cell lines. Immunohistochemical expression of MKP-1 protein was reduced in tissue from LMP tumors and invasive ovarian carcinomas compared to normal ovaries and cystadenomas. A moderate to strong expression of MK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 18 publications
4
73
0
Order By: Relevance
“…V Moncho-Amor et al several malignancies, including breast, prostate and NSCLC (Loda et al, 1996;Denkert et al, 2002;Chattopadhyay et al, 2006). Lung cancer is a major cause of cancer mortality and accounts for about 20% of all cancer deaths worldwide.…”
Section: Dusp1 Participates In Tumor Progression In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…V Moncho-Amor et al several malignancies, including breast, prostate and NSCLC (Loda et al, 1996;Denkert et al, 2002;Chattopadhyay et al, 2006). Lung cancer is a major cause of cancer mortality and accounts for about 20% of all cancer deaths worldwide.…”
Section: Dusp1 Participates In Tumor Progression In Nsclcmentioning
confidence: 99%
“…DUSP1 is a nuclear mitogen and stress-inducible MAP kinase phosphatase highly expressed in different types of human tumors, including non-small-cell lung cancer (NSCLC), breast, ovarian, bladder, osteosarcoma and in prostate cancer in early stages of disease (Loda et al, 1996;Denkert et al, 2002;Chattopadhyay et al, 2006). We have previously demonstrated that DUSP1 has an essential function in NSCLC biology (Chattopadhyay et al, 2006), both in tumor growth and in response to cisplatin treatment.…”
mentioning
confidence: 99%
“…Inhibition of MKP1 expression is able to sensitize DU145 cells to Fas ligand and TNF-a induced apoptosis (Srikanth et al, 1999), as well as in renal cancer cells (Mizuno et al, 2004). Overexpression of MKP1 in primary human ovarian carcinoma correlates with shorter progressionfree survival times (Denkert et al, 2002) and, finally, increases the expression of MKP1 and MKP2 correlated with low JNK activity in breast cancer (Wang et al, 2003). Evidence presented recently demonstrated the MKP1 deficient MEFs are also more sensitive to apoptosis induction by anysomicin than parental cells, owing to a higher activation of JNK and p38 (Wu and Bennett, 2005).…”
Section: Mkp1 Controls Sensitivity To Cisplatin In Nsclc S Chattopadhmentioning
confidence: 99%
“…Although MKP1 levels in normal cells are low, increased levels of MKP1 have been found in human ovarian carcinoma, breast and prostate cancer (Srikanth et al, 1999;Denkert et al, 2002;Wang et al, 2003). In this report, we have investigated the expression and function of MKP1 in the chemotherapy response to cisplatin in NSCLC.…”
Section: Introductionmentioning
confidence: 97%
“…For example, high levels of MKP-1 have been found in prostate (4), gastric (5), breast (6), and pancreatic cancer (7). In ovarian cancer samples, MKP-1 expression was correlated with decreased progression-free survival (8). High levels of MKP-1 expression were also found in the early phases of prostate, colon, and bladder carcinogenesis (9).…”
Section: Mitogen-activated Protein Kinase Phosphatase (Mkp)mentioning
confidence: 99%